2016
DOI: 10.1097/md.0000000000004982
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of NOS1 exon18, NOS1 exon29, ABCB1 1236C/T, and ABCB1 3435C/T polymorphisms with the risk of Parkinson's disease

Abstract: Background:Parkinson's disease (PD) is the second most frequent neurodegenerative disorder. Previous publications have investigated the association of NOS1 and ABCB1 polymorphisms with PD risk. However, those studies have provided some contradictory results.Methods:Literature searches were performed using PubMed, Embase, PDgene, China National Knowledge Infrastructure database, and Google Scholar. Odds ratios (ORs) with 95% confidence intervals (CIs) were applied to evaluate the strength of association.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Similarly, Contino and colleagues, aiming at developing compounds able to up-regulate P-gp expression in order to reach a detoxification effect of the central nervous system (CNS) caused by AB accumulation, used an ex vivo model and identified a new benzopyrane derivative as a P-gp inducing agent [ 87 ]. Parkinson’s disease (PD) is the second most frequent neurodegenerative disorder [ 88 ]. For the same reason as that referred for AD, ABC carriers seem to be involved in PD pathophysiology since they have an important role in transporting out of the brain α-synuclein, one of the dominant proteins found in Lewy Bodies, a pathological hallmark of Lewy body disorders, including PD [ 89 ].…”
Section: Overview Of the Abc Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Contino and colleagues, aiming at developing compounds able to up-regulate P-gp expression in order to reach a detoxification effect of the central nervous system (CNS) caused by AB accumulation, used an ex vivo model and identified a new benzopyrane derivative as a P-gp inducing agent [ 87 ]. Parkinson’s disease (PD) is the second most frequent neurodegenerative disorder [ 88 ]. For the same reason as that referred for AD, ABC carriers seem to be involved in PD pathophysiology since they have an important role in transporting out of the brain α-synuclein, one of the dominant proteins found in Lewy Bodies, a pathological hallmark of Lewy body disorders, including PD [ 89 ].…”
Section: Overview Of the Abc Transportersmentioning
confidence: 99%
“…However, in many cases, the reported effects of these polymorphisms have been conflicting. A recently published meta-analysis conducted by Huang and colleagues suggested that ABCB11236C/T variants might play a role in the risk of PD, whereas ABCB13435C/T polymorphisms might not contribute to PD susceptibility [ 88 ]. On the other hand, a study showed that LRP1, but not P-gp, may be involved in α-synuclein efflux across BBB [ 89 ].…”
Section: Overview Of the Abc Transportersmentioning
confidence: 99%
“…VIP (vasoactive intestinal peptide) [336], CD40 [337], CCL2 [338], DKK2 [339], ACE (angiotensin I converting enzyme) [340], KCNN4 [341], A2M [342], CDKN2A [343], MYD88 [344], TLR6 [345], ANXA1 [346], SPHK1 [347], CACNA1A [348], SLITRK2 [349], IL33 [350], CAT (catalase) [351], GPR78 [352], ANG (angiogenin) [353], GDF15 [354] and ADH1B [355] might be a potential therapeutic targets for neurodegenerative diseases treatment. At present, abnormal expression of VIP (vasoactive intestinal peptide) [356], HFE (homeostatic iron regulator) [357], CCL2 [358], HLA-DRA [359], TFF3 [360], NOS1 [361], NPPC (natriuretic peptide C) [362], ACE (angiotensin I converting enzyme) [363], GSDMD (gasdermin D) [364], A2M [365], PLXNA4 [366], CD44 [367], CASP1 [364], DRD3 [368], UNC5C [369], CAV1 [370], SPHK1 [371], CD163 [372], RPH3A [373], HGF (hepatocyte growth factor) [374], CCKBR (cholecystokinin B receptor) [375], TNFSF9 [376], MEG3 [377], GPR78 [378], NEUROG2 [379], ANG (angiogenin) [380], GDF15 [381], UNC5A [382], SLC1A2 [383], DRD2 [384], GPR143 [385], RASGRP1 [386] and MOBP (myelin associated oligodendrocyte basic protein) [387] have been found in a Parkinson’s disease. VIP (vasoactive intestinal peptide) [388], CD40 [389], WT1 [390], HFE (homeostatic iron regulator) [391], TAC1 [392], AQP5 [393], WNT2B [394], RUNX1 [395], NOS1 [396], DKK2 [339], ADAM12 [397], ABCG2 [398], NINJ2 [399], ACE (angiotensin I converting enzyme) [400], PRKCB (protein kinase C beta) [401], A2M […”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that children with the CC genotype exhibited shorter times of induction, respiration recovery, eye-opening, and extubation compared to the MDR1 1236C > T CT + TT genotype. MDR1 is something that can be found in a variety of tissues including gastrointestinal and nasal respiratory mucosa, liver, kidneys, placenta, and the adrenal cortex [ 22 ]. It is known that Propofol and remifentanil have been extensively applied for anesthesia, analgesia, and procedural sedation [ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%